Action Research on Documenting Learner Outcomes: Can We Move Beyond the Workforce Investment Act? - Mary Beth Bingman (Adult Education Research Conference, 2000)
An action research project with three adult basic education programs focused on ways to document the invisible outcomes in learners’ lives. It has led to increased understanding of how programs might identify and measure those outcomes not captured by traditional assessments.